Optically Stimulated Luminescence Dating Revealed the Late Quaternary Coastal Sediments in Songkhla Coast, Thailand - Laerosa, Araf; Pradit, Siriporn; Luengchavanon, Montri; Noppradit, Prakrit (Burapha Science Journal, 2024)
Background and Objectives : Coastal sediments along the Songkhla coast still lack chronological data to describe their evolution. The objective of this study was to determine the chronological ages of the lagoonal side of the Songkhla coastline area, with the purpose of conducting a preliminary investigation into the development of the Songkhla lagoon. Methodology : The topographic map of the coastal sediments that were classified early were taken with the real-time kinematic survey by the Global Navigation Satellite System. Samples were taken from the old ridges and plains behind the ridges using a light-blocking (PVC) cylinder tube and dated by optically stimulated luminescence (OSL) with the single aliquot regenerative dose protocol. Main Results : A field survey by GNSS-RTK confirmed the two old ridges and plains parallel to the Songkhla lagoon coast in Hatyai district. The dating results were 10.0, 30.5, 39.2 ka (thousand years), and a saturated equivalent dose sample. Conclusions : Quartz OSL dating revealed that the inner old ridge and plain behind the ridge were deposited during the humid period approximately 30–40 ka before the drought period in the late glacial maximum (LGM). At the same time, the youngest sediment here was the outer plain behind the ridge that was deposited 10 ka ago when the sea level transgressed in the early Holocene. Since then, only tidal flat sediment has been found on the lagoon coast. However, in this area, there was a hiatus during LGM.